Antigen targeting and anti-tumor activity of a novel anti-CD146 212Pb internalizing alpha-radioimmunoconjugate against malignant peritoneal mesothelioma - Kim Lindland; Marion Masitsa Malenge; Ruth Gong Li; Roxanne Wouters; Tina Bjørnlund Bønsdorff; Asta Juzeniene; Srdan M. Dragovic (Scientific Reports)
Abstract Malignant mesothelioma, a highly aggressive cancer that primarily affects the serosal membranes, has limited therapeutic options, particularly for cavitary tumors, such as peritoneal and pleural malignant mesothelioma. Intracavitary administration of a radioimmunoconjugate to locally target mesothelioma cancer cells has been proposed as a treatment. CD146, upregulated in mesothelioma but not in healthy tissues, is a promising therapeutic target. This study characterized CD146 expression and binding/internalization kinetics of the CD146-targeting antibody OI-3 coupled with 212Pb (212Pb-TCMC-OI-3) in human mesothelioma cells. Flow cytometry showed that both chimeric (chOI-3) and murine (mOI-3) antibodies rapidly bound and internalized within 1–6 h in MSTO-211H cells. 212Pb-TCMC-chOI-3 exhibited 3.1- to 13.7-fold and 3.1- to 8.5-fold increased internalized 212Pb and 212Bi atoms per cell at 2 and 24 h, respectively, compared to isotype control, underscoring enhanced internalization efficiency. Intraperitoneal administration of 212Pb-TCMC-mOI-3 to mice with intraperitoneal MSTO-211H xenografts improved median survival by a ratio of 1.3 compared to non-binding 212Pb-TCMC-mIgG1. The ability of 212Pb-TCMC-mOI-3 to target and inhibit the growth of intraperitoneal mesothelioma xenografts supports targeted radionuclide therapy’s efficacy for metastatic peritoneal mesothelioma. This study highlights the potential of localized CD146-targeted radioimmunotherapy for malignant mesothelioma, offering a new avenue for improving patient outcomes.